Improved Practices for Temporary Work Zone Guide Signs. Issue 1 (January 2023) - Theiss, LuAnn; Higgins, Laura; Ullman, Gerald L.
Freeway reconstruction projects often involve adding lanes and improving entrance and exit ramps. Sign supports for overhead guide signs are sometimes removed early in the project to make way for construction activities. In addition, roadside guide signs may need to be relocated and replaced with temporary guide signs. The Manual on Uniform Traffic Control Devices provides guidance for work zone guide signs in Part 6, stating that temporary guide signs shall have black legend and border on an orange background. But permanent guide signs follow Part 2 of the MUTCD, which prescribes white legend and border on a green background for guide signs in general. Thus, many long-term freeway work zones may have guide signs in both color schemes that change throughout the project as the construction work progresses. The constrained conditions often seen in these work zones can also result in guide signs that use a variety of fonts, font sizes, sign sizes, and placement positions. This paper describes the human factors study that was performed to assess motorist understanding of various work zone guide signage strategies. Based on the results, the researchers were able to develop recommendations for long-term work zone guide sign design and placement to improve uniformity for the traveling public.